Moral Psychology Today Essays on Values, Rational Choice, and the Will - Chan, David K. (Philosophical Studies Series, 2008)
This book brings together in one volume some of the very latest developments in moral psychology that were presented at a major American conference in 2004. Moral psychology is a broad area at the intersection of moral philosophy and philosophy of mind and action. Essays in this collection deal with most of the central issues in moral psychology that are of interest to a large number of philosophers today, including important questions in normative ethical theory, meta-ethics, and applied ethics. Each essay has been provided with its own list of references, and all essays are carefully introduced by the editor and organized thematically. Many of the ideas are introduced here in published form for the first time by an international cast of established and up-and-coming philosophers. Because of its breadth and topicality, this book will benefit professional philosophers grappling with the important questions that are addressed here, and also philosophy students approaching moral psychology for the first time in a graduate or upper undergraduate class who need an up-to-date and wide-ranging approach to the subject. This is a book that will make an invaluable contribution to philosophical debate for many years to come.